Morphological and physiological responses of apple trees under photoselective colored nets - Bastias, Richard <1973> (Alma Mater Studiorum - Università di Bologna, 2011)
In recent years and thanks to innovative technological advances in supplemental lighting sources and photo-selective filters, light quality manipulation (i.e. spectral composition of sunlight) have demonstrated positive effects on plant performance in ornamentals and vegetable crops. However, this aspect has been much less studied in fruit trees due to the difficulty of conditioning the light environment of orchards. The aim of the present PhD research was to study the use of different colored nets with selective light transmission in the blue (400 – 500 nm), red (600 – 700 nm) and near infrared (700 – 1100 nm) wavelengths as a tool to the light quality management and its morphological and physiological effects in field-grown apple trees. Chapter I provides a review the current status on physiological and technological advances on light quality management in fruit trees. Chapter II shows the main effect of colored nets on morpho-anatomical (stomata density, mesophyll structure and leaf mass area index) characteristics in apple leaves. Chapter III provides an analysis about the effect of micro-environmental conditions under colored nets on leaf stomatal conductance and leaf photosynthetic capacity. Chapter IV describes a study approach to evaluate the impact of colored nets on fruit growth potential in apples. Summing up results obtained in the present PhD dissertation clearly demonstrate that light quality management through photo-selective colored nets presents an interesting potential for the manipulation of plant morphological and physiological traits in apple trees. Cover orchards with colored nets might be and alternative technology to address many of the most important challenges of modern fruit growing, such as: the need for the efficient use of natural resources (water, soil and nutrients) the reduction of environmental impacts and the mitigation of possible negative effects of global climate change.